After the fall : opportunities and strategies for real estate investing in the coming decade - Bergsman, Steve (Wiley, 2009)
Praise for After The Fall. "Steve Bergsman provides his readers with one of the most comprehensive, yet concise overviews of real estate and all its property types.".?Christopher Macke, Vice President, GE Real Estate. "This is an extraordinary work of detailed research and compelling writing. I've never seen the subject presented in such a cogent and skillful manner.".?Phil Hall, editor, Secondary Marketing Executive. "The way out of the financial crash of 2007/2008 will come through skilled operations, astute investing, and the ability of real estate practitioners t.